Adsorptive batch and column studies of Congo Red onto gulmohar leaf powder - Patel, Himanshu (European Journal of Chemistry, 2018)
The present manuscript describes the adsorptive batch and column treatment of synthetic Congo Red dye onto naturally prepared adsorbents viz. gulmohar leaf powder and activated gulmohar leaf powder using sulfuric acid. The surface characterizations of naturally prepared adsorbents were performed by various sophisticated analytical techniques. Effect of various process parameters like adsorbent dosage, temperature, initial concentration, and pH for batch study; and flow rate and bed height for column study are explored. All batch adsorption data are analyzed using Freundlich and Langmuir adsorption isotherm model. The Thomas, Yoon-Nelson, Adams and Bohart, and Bed Depth Service Time model are applied to predict the breakthrough curves and to determine the characteristic parameters of the column useful for process design. Activated gulmohar leaf powder is more feasible adsorbent compared to normal gulmohar leaf powder. Maximum adsorption capacity related to Adams and Bohart model; and Langmuir isotherm was found to be 919.4 mg/L; and 434.7 mg/g, respectively, for activated gulmohar leaf powder.